Imaginários urbanos e a construção paisagística na cidade de Itaúna/MG - Alessandra Claudia Cabanelas da Silva (2016)
This present study investigated the landscape formation of the city of Itaúna (MG), which has revealed noticeable changes, with accelerated change in the conformation of its urban environment. It sought to know the landscape perception revealed by the imaginary of various actors who build the social environment at different times, investigating the attributes of the new urban landscapes of Itauna that are being settled. The spatial study area is the downtown area, which suffered a fast process of landscape change, especially after the term of the Master Plan of 2008. The study sought to interpret how residents evaluate the changes in the landscape quality of the city and the role of many actors involved in its construction and management (State, businessmen, residents and technicians). The methodological procedures, developed from previous theoretical and conceptual basis, which discussed the concept of landscape and its attributes based on several authors, allowed to build a matrix to read the landscape formation of a place, highlighting the role of imaginary and ideology in the urban landscape construction. Based on the matrix of analysis, it determined the guidelines for the formulation of questionnaires applied in the studies, which emphasized the understanding of landscape formation process occurred over time. The interpretation of the data permitted to evaluate that the perception of the city resident is much determined by the imaginary and social representations, revealing a constant conflict relationship with their own city. At the same time they recognize in the verticalization of a sign of "development and progress", the citizens express a nostalgic feeling of a city of the past, which, according to them, showed a better dialogue with nature. The results of the group of businessmen and technicians revealed a contradiction on how they act and what they think. They act to verticalize, thicken, and get the highest profit from their activity and use the pressure of economic power for laws favoring themselves, to the detriment of the collectivity. But on their speech, however, they recognize that the landscape of today has been very negative. The results reveal the importance of research in urban studies, the urban and imaginary ghosts that engender the landscape design of places.